Pengaruh Motivasi Dan Pengembangan Karir Terhadap Kinerja Karyawan: Studi Kasus Pada Salah Satu Perusahaan Layanan Keuangan Milik Negara Wilayah Bandung - Martina Isnan; Soelaiman Sukmalana; Dhea Perdana Coenraad; Windi Matsuko Danasasmita (Acman: Accounting and Management Journal, 2022)
Researchers researched to determine the effect of Motivation and Career Development on Employee Performance of a financial service company in the Bandung area. Moreover, this research analyzes the factor that has the most dominant influence between Motivation and Career Development on Employee Performance of a financial service company in the Bandung area; as many as 50 employees are the object of research using a questionnaire. Based on path analysis research, the variables of Motivation and Career Development on Employee Performance of a financial service company in the Bandung area are declared valid. Therefore, the conclusions and considerations related to the research results pay attention to Motivation and Career Development to Improve Employee Performance. The results of the study show that motivation (X1) has a significant effect on employee performance (Y). then Career Development (X2) significantly influences Employee Performance (Y). Therefore, motivation (X1) and Career Development (X2) have a significant effect on Employee Performance (Y). In increasing employee motivation, companies should pay more attention to employee needs and career development because it impacts employee morale by improving the policy system and paying attention to cost-effectiveness. Furthermore, when employees experience career development, it certainly makes them feel they have adequate abilities to complete their work tasks in the company. These factors affect employee motivation to be more advanced and can help improve employee performance even better.